2014
DOI: 10.1200/jop.2014.001388
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity, Chemotherapy Toxicity, and Outcomes Among Older Women Receiving Adjuvant Chemotherapy for Breast Cancer on a Clinical Trial: CALGB 49907 and CALGB 361004 (Alliance)

Abstract: Purpose: We evaluated associations among comorbidity, toxicity, time to relapse (TTR), and overall survival (OS) in older women with early-stage breast cancer receiving adjuvant chemotherapy. Cancer and Leukemia Group B 49907 (Alliance) randomly assigned women Ն 65 years old with stages I-III breast cancer to standard adjuvant chemotherapy or capecitabine. We reviewed data from 329 women who participated in the quality of life companion study CALGB 70103 and completed the Physical Health Subscale of the Old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 33 publications
6
51
0
Order By: Relevance
“…Similar results were reported by Klepin et al (2014), who showed that both chemotherapy tolerance and DFS were not negatively affected by comorbidity. However, when interpreting the data published by Klepin et al, it should be noted that patients in their study had an excellent performance status.…”
Section: Discussionsupporting
confidence: 78%
“…Similar results were reported by Klepin et al (2014), who showed that both chemotherapy tolerance and DFS were not negatively affected by comorbidity. However, when interpreting the data published by Klepin et al, it should be noted that patients in their study had an excellent performance status.…”
Section: Discussionsupporting
confidence: 78%
“…As a result, there are limited data available on the impact of comorbidities on treatment complications among breast cancer patients and the underlying reasons for failure to complete treatment. A recent study, for instance, that evaluated the impact of self-reported comorbidities among older women receiving adjuvant chemotherapy for breast cancer while in the CALGB 49907 and CALGB 361004 clinical trials found comorbidity to be associated with shorter overall survival, but not with toxicity or time to relapse (Klepin et al 2014 ), possibly because these women all had good functional status with less severe comorbidity at the time of enrollment since eligible patients could not have a medical condition that would make the protocol hazardous (Klepin et al 2014 ). Greater understanding of the degree to which various comorbidities affect breast cancer treatment and ultimately breast cancer survival is a research priority, and can be addressed through both observational studies as well as randomized trials designed to more broadly examine the potential impact of new breast cancer treatments across the entire targeted patient population.…”
Section: Effect Of Comorbidities During and After Breast Cancer Treatmentioning
confidence: 98%
“…(23, 24) Similarly, in a recent secondary analysis of comorbidity in older adults with breast cancer, no association with toxicity was found. (25) In a study evaluating chemotherapy related hospitalizations, severe comorbid illness (CCI score ≥3) increased the risk of hospitalization nearly 10 fold and was the strongest predictor of hospitalization. (21) Moreover, patients with comorbidities are less likely to complete chemotherapy compared to patients without comorbidity.…”
Section: Relevance In Cancermentioning
confidence: 99%